Effectiveness of Number Bag Games in Improving Number Recognition Among Preschoolers: A Qualitative Study in Rural Indonesia - Iz, Nailufar Lailatul; Rouf, Abdul Muiz; Sopiah, Cucu (Journal of Innovation and Research in Primary Education, 2025)
Early childhood represents a critical period for developing foundational numeracy skills, yet traditional worksheet-based approaches often fail to engage children's developmental needs and natural learning inclinations. This study investigated the effectiveness of number bag media in improving number recognition skills among Group A children at Al-Hidayah Early Childhood Education Center. A qualitative descriptive design was employed with 11 purposively selected children aged 4-5 years. Data were collected through systematic classroom observations, semi-structured interviews with teachers, and documentary analysis over two consecutive days. Children's performance was assessed across five indicators: counting sequences, recognizing number forms, ordering numbers, pairing quantities with symbols, and writing number symbols, using four developmental categories. Post-intervention assessment revealed measurable improvements in number recognition abilities. The proportion of children classified as not yet developed decreased from 27.3% to 9.1%, while those beginning to develop increased from 27.3% to 45.5%. Children demonstrated enhanced engagement and enthusiasm when interacting with concrete manipulative materials. Number bag media effectively enhances early number recognition skills by providing developmentally appropriate, play-based learning experiences. The intervention's accessibility and low-cost construction make it suitable for widespread implementation in resource-constrained educational settings.